Pengaruh Pengalaman dan Pelatihan Terhadap Kinerja Tenaga Penjualan dengan Penjualan Adaptif Sebagai Variabel Intervening: Studi pada BNI Cabang Kebumen - Irfan Helmy; Aji Hidayat (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out about experience and training on sales force performance with adaptive selling as an intervening variable. The exogenous variables in this research are experience and training, the mediating variable is adaptive selling, while the endogenous variable is sales force performance. The sampling technique in this research used a saturated sampling technique, namely all BNI Kebumen Branch sales personnel totaling 45 people. The data collection technique uses a questionnaire which is then analyzed using SEM using Smart PLS 4.0. The research results found that there is a direct influence of experience, training and adaptive selling on sales force performance. Experience and training have a direct influence on adaptive sales. Adaptive selling is able to mediate the influence of experience and training on sales force performance.